Transgressive Character of the Femme Fatale Image in Oles Ulianenko’s Novel “Seraphim” - Shteinbuk, Feliks (Respectus Philologicus, 2022)
The article is dedicated to one of the most talented and the most controversial modern Ukrainian writers Oles Ulianenko. However, his literary works did not receive the appropriate professional interpretation because the literary scholars and critics applied either the erroneous or unproductive professional methodology for many objective and subjective reasons. As a result, the writer’s works remain unread or read in an arguable way. Taking one of the most contentious novels of O. Ulianenko’s “Seraphim” as an example for analysis, the aim of this article is to suggest an alternative variant of theoretical and literary analysis based on the corporal-mimetic method to interpret fiction works. Due to the chosen approach, it is possible to draw the conclusion that the image of Seraphim is the image which only seemingly claims the status of the femme fatale; actually, the content of this image is а constant overcoming social, property, status, space, gender, corporal, sexual and other rules and norms. It says about overcoming in order to overcome, about complete overcoming which can be stopped only by death which, being unmotivated, is another variant of phenomenal, namely feminine transgression.